A mediating analysis of mental health impacts in the relationship of digital device and digital communication with academic performance - Ting Tin Tin; Ooi Yih Ming; Yap Li Jin; Ng Wei Sheng; Khor Qian Rou; Wan Nor Al-Ashekin Wan Husin; Ali Aitizaz; Lee Kuok Tiung; Sunday A. Afolalu; Umar Farooq Khattak (Scopus, 2024)
In this digital era, smartphones and social media play an irreplaceable role in the lives of youth. Whether for studying, entertaining, or relaxing, they serve various purposes as needed. This study analyzes the relationship between digital devices and digital communication with mental health and academic performance, along with mediating variables such as CGPA, smartphone and social media usage habits, and current mental states. Seven variables and a sample size of 104 were collected to identify how smartphone and social media usage habits affect the mental state of youth as well as their academic performance. Pearson Correlation and mediating analysis (PROCESS MACRO) were used to analyze the sampled data to find relationships between the variables. This research highlights the relationship between smartphone and social media usage and the mental health states of youth and their academic performance. The results of the Pearson Correlation and Mediating Analysis have shown that 10 of the hypotheses are accepted and 8 of the hypotheses are rejected. This study significantly contributes to understanding of the impact of excessive digital usage on youth mental health in Malaysia, providing crucial insights for future research.